Oil and Gas Management and Corporate Social Responsibility Model Based on Existing Laws - Nurdin MH; Adwani; Sanusi; Azhari Yahya (Universitas Airlangga, 2025)
In the past, the Central Government managed oil and natural gas in a centralized manner without involving the Government of Aceh. However, currently, Aceh has its authority in managing the upstream oil and gas sector. This authority is regulated in Government Regulation Number 23 of 2015 concerning the Joint Management of Oil and Gas in Aceh. Based on special autonomy, the Government of Aceh can regulate CSR based on local wisdom whose programs are compiled by the community around the company itself so that it can increase the economic growth of the community around the company in a sustainable manner. Using normative legal methods, this research examines the current practice of CSR at PT Medco E&P Malaka and proposes for its improvement. The research approach used is statutory approach. The research results show that the existence of PT Medco E&P Malaka CSR is unable significantly contribute to Local Own Revenue and create sustainable economic growth for the people are living around the company. This is because the implementation of CSR so far is top-down and only partially based on programs created by the community based on the community's actual needs. A CSR Forum is needed as a new CSR model responsible for designing and implementing various CSR based on a real need assessment of the local community.